2010
DOI: 10.1016/s0140-6736(10)60239-5
|View full text |Cite|
|
Sign up to set email alerts
|

Carotid artery stenting compared with endarterectomy in patients with symptomatic carotid stenosis (International Carotid Stenting Study): an interim analysis of a randomised controlled trial

Abstract: SummaryBackgroundStents are an alternative treatment to carotid endarterectomy for symptomatic carotid stenosis, but previous trials have not established equivalent safety and efficacy. We compared the safety of carotid artery stenting with that of carotid endarterectomy.MethodsThe International Carotid Stenting Study (ICSS) is a multicentre, international, randomised controlled trial with blinded adjudication of outcomes. Patients with recently symptomatic carotid artery stenosis were randomly assigned in a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
196
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,085 publications
(213 citation statements)
references
References 20 publications
7
196
1
2
Order By: Relevance
“…According to the results of recent randomized clinical trials on the safety and efficacy of endarterectomy versus CAS for symptomatic carotid stenosis, the risk of any periprocedural stroke or death is higher with CAS than with endarterectomy [11,12,13,14,15,16]. However, a head-to-head comparison of endarterectomy versus CAS to identify the best modality for the treatment of all patients may not comply with the demands for individual treatment decisions in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of recent randomized clinical trials on the safety and efficacy of endarterectomy versus CAS for symptomatic carotid stenosis, the risk of any periprocedural stroke or death is higher with CAS than with endarterectomy [11,12,13,14,15,16]. However, a head-to-head comparison of endarterectomy versus CAS to identify the best modality for the treatment of all patients may not comply with the demands for individual treatment decisions in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Carotid stenting has emerged as a potential alternative to endarterectomy. The risk of periprocedural stroke is higher with stenting than with endarterectomy when done in patients judged suitable for either procedure [4,5,6,7]. However, the risks of both procedures vary with patient characteristics and may differ between specific groups of patients [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…CREST (Carotid Revascularization Endarterectomy versus Stenting Trial)10 reported the shortest median interval; this was still 22 days for CEA and 18 days for CAS. In all except two RCTs, the mean delay from the index event to revascularization was greater than 1 month9, 12, 14. Even in studies that mostly revascularized sooner after the index event, the mean delay was above the 2‐week threshold3, 10.…”
mentioning
confidence: 88%
“…Of the 12 RCTs3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 that have compared carotid endarterectomy (CEA) with carotid artery stenting (CAS) in patients with significant carotid stenosis, only five3, 9, 10, 12, 14 provided information on the time from the index event to revascularization. CREST (Carotid Revascularization Endarterectomy versus Stenting Trial)10 reported the shortest median interval; this was still 22 days for CEA and 18 days for CAS.…”
mentioning
confidence: 99%